2016
DOI: 10.1017/apr.2016.11
|View full text |Cite
|
Sign up to set email alerts
|

Population models at stochastic times

Abstract: Abstract. In this article, we consider time-changed models of population evolution X f (t) = X (H f (t)), where X is a counting process and H f is a subordinator with Laplace exponent f . In the case X is a pure birth process, we study the form of the distribution, the intertimes between successive jumps and the condition of explosion (also in the case of killed subordinators). We also investigate the case where X represents a death process (linear or sublinear) and study the extinction probabilities as a func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The case for stochastic clearing processes is considered by [15]. Relevant also are [16][17][18][19][20]. For references on sample-path analysis, the reader is referred to [1,2,16,[21][22][23][24][25].…”
Section: =0mentioning
confidence: 99%
“…The case for stochastic clearing processes is considered by [15]. Relevant also are [16][17][18][19][20]. For references on sample-path analysis, the reader is referred to [1,2,16,[21][22][23][24][25].…”
Section: =0mentioning
confidence: 99%
“…Saeedian et al [36] showed how another memory functional of the process can lead to replacing the integer derivatives with Caputo fractional derivatives. In this paper, we show how Caputo fractional differential equations follow naturally from fractional stochastic processes like those introduced in [37][38][39][40][41][42][43][44][45][46]. Then we show that for different data sets, FDE models fit the data better for some epidemics whereas ODE models fit better for others.…”
Section: Introductionmentioning
confidence: 99%
“…Saeedian et al [36] showed how another memory functional of the process can lead to replacing the integer derivatives with Caputo fractional derivatives. In this paper, we show how Caputo fractional differential equations follow naturally from fractional stochastic processes like those introduced in literature [37][38][39][40][41][42][43][44][45][46]. We then compare transient and long term dynamics between the FDE and ODE models while fitting them to three different data sets.…”
Section: Introductionmentioning
confidence: 99%